2006
DOI: 10.4171/028-1/4
|View full text |Cite
|
Sign up to set email alerts
|

Hopf algebras in renormalization theory: locality and Dyson–Schwinger equations from Hochschild cohomology

Abstract: ABSTRACT. In this review we discuss the relevance of the Hochschild cohomology of renormalization Hopf algebras for local quantum field theories and their equations of motion. CONTENTS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
224
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(228 citation statements)
references
References 37 publications
(115 reference statements)
4
224
0
Order By: Relevance
“…For overlapping sub-divergencies, there are some challenges but the corresponding tree representation could be a linear combination of decorated rooted trees. We refer the reader to [1,12,23,24] for further details in this issue.…”
Section: Feynman Diagrams Under a New Combinatorial Settingmentioning
confidence: 99%
See 4 more Smart Citations
“…For overlapping sub-divergencies, there are some challenges but the corresponding tree representation could be a linear combination of decorated rooted trees. We refer the reader to [1,12,23,24] for further details in this issue.…”
Section: Feynman Diagrams Under a New Combinatorial Settingmentioning
confidence: 99%
“…The completion of the Hopf algebra H with respect to this topology is the extended Hopf algebra H = n≥0 H n which has elements of the form n≥0 Γ n such that Γ n ∈ H n . It is shown that solutions of combinatorial DSEs belong to this completed Hopf algebra [1,19,25,26,40,41]. On the other side, for each n, X n is a finite Feynman diagram which guarantees the finiteness of the terms Y n s. Each Y n could be constructed from Y n−1 by a growing (not generally uniform) attachment graph sequence.…”
Section: Corollary 44 There Exists a Complete And Compact Metric Stmentioning
confidence: 99%
See 3 more Smart Citations